Activity-based costing in the after press services industry - Suntichai Shevasuthisilp (2018)
This research was conducted to apply activity-based costing (ABC) in an after press service company in Chiang Mai province, Thailand. The company produces all of its products by one-stop service (such as coating, stitching, binding, die cutting, and gluing). All products are made to order, and have different sizes and patterns. A strategy of low price is used to compete in the marketplace. After cost analysis, the study found that the company has high overhead (36.5% of total cost). The company's problem is its use of traditional cost accounting, which has low accuracy in assigning overhead costs. If management uses this information when pricing customer orders, losses may occur because real production costs may be higher than the selling price. Therefore, the application of ABC in cost analysis can help executives receive accurate cost information; establish a sound pricing strategy; and improve the manufacturing process by determining work activities which have excessively high production costs. According to this research, 6 out of 56 items had a production cost higher than the selling price, leading to losses of 123, 923 baht per year. Methods used to solve this problem were: reducing production costs; establishing suitable prices; and creating a sales promotion with lower prices for customers whose orders include processes involving unused capacity. These actions will increase overall sales of the company, and allow more efficient use of its machinery. © 2009 American Institute of Physics.